Firms Far Up! Productivity, Agglomeration and High-Growth Firms in Ethiopia - Grover, Arti (World Bank, Washington, DC, 2020)
High-growth firms have been widely studied in advanced countries, but little is known about such stellar performers in Africa. Using establishment-level data from Ethiopia, this paper finds that the incidence of high-growth firms stands at an average of 7 percent, a figure comparable to that of advanced countries. High-growth episodes are short-lived, and the likelihood of survival or a subsequent episode is not any higher for high-growth firms. It is difficult for firms to sustain high growth, and the likelihood of a repeated episode is low. There is only a 6.5 percent chance that a manufacturing plant in Ethiopia will repeat a high-growth event in the subsequent three-year period. This likelihood is not greater than that of plants that did not experience high growth in the previous period. The paper explores the drivers of high growth and finds a tight link between exemplary performance and initial plant productivity, which is robust to many controls, including plant location. Plants located in Ethiopia's capital city or agglomerations have a higher probability of high growth. And high growth in plant employment is found to be self-reinforcing, that is, past high-growth experience is positively and significantly associated with subsequent growth in firm productivity.